Macrophage migration inhibitory factor polymorphisms do not predict therapeutic response to glucocorticoids or to tumour necrosis factor α-neutralising treatments in rheumatoid arthritis. Issue 11 (24th April 2007) - Radstake, Timothy R D J; Fransen, Jaap; Toonen, Erik J M; Coenen, Marieke J H; Eijsbouts, Agnes E; Donn, Rachelle; van den Hoogen, Frank H J; van Riel, Piet L C M
Abstract : Background: Macrophage migration inhibitory factor (MIF) is an inflammatory mediator associated with RA severity. In various diseases, MIF polymorphisms are associated with clinical response glucocorticoid (GC) treatment. It is unclear whether MIF polymorphisms determine GC response in rheumatoid arthritis (RA) and to other RA treatments. Therefore, the question of whether two functional variants in MIF are associated with the response to tumour necrosis factor (TNF)α-neutralising and GC treatments in RA was investigated. Methods: Data from two cohorts of an RA registry were used. For patients who started with TNFα-neutralising (infliximab) or GC treatment, courses with a duration of at least 3 months were included and response to TNFα blockers or GC was calculated according to the European League Against Rheumatism response criteria. MIF −173G→C genotyping was achieved using an assay-on-demand allelic discrimination assay, and alleles of the CATT repeat element were identified using a fluorescently labelled PCR primer and capillary electrophoresis. Logistic-regression modelling was used for the statistical analysis. Results: In total, 192 courses of oral prednisone or methylprednisolone injections in 98 patients with RA and 90 patients with RA who were on TNFα-neutralising treatments were documented. In all, 27% of the patients with RA were found to be heterozygous for seven CATT repeats (CATT7 ) and 31% were heterozygous for −173C. Respectively, 4% and 6% of the patients with RA were homozygous for the MIF CATT7 repeat or the MIF −173C allele. Carrier status and homozygosity for CATT7 repeat and the MIF −173C allele were not associated with response to GC (odds ratios (ORs) close to 1) or to TNFα-neutralising treatment (ORs close to 2). Conclusion: The MIF-CATT7 repeat and the MIF−173G→C functional variant are not strongly associated with a decreased clinical response to TNFα-neutralising or GC treatment in RA.